2003
DOI: 10.1053/jhep.2003.50211
|View full text |Cite
|
Sign up to set email alerts
|

Propranolol Plus Placebo Versus Propranolol Plus Isosorbide–5–Mononitrate in the Prevention of A First Variceal Bleed: A Double–Blind Rct

Abstract: Nonselective ␤-blockers are very effective in preventing first variceal bleeding in patients with cirrhosis. Treatment with isosorbide-5-mononitrate (IS-MN) plus propranolol achieves a greater reduction in portal pressure than propranolol alone. The present multicenter, prospective, double-blind, randomized, controlled trial evaluated whether combined drug therapy could be more effective than propranolol alone in preventing variceal bleeding. A total of 349 consecutive cirrhotic patients with gastroesophageal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
87
2
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(94 citation statements)
references
References 33 publications
(43 reference statements)
4
87
2
1
Order By: Relevance
“…69 These results were maintained after 55 months of follow-up, without differences in survival. 70 However, 2 more recent larger doubleblinded, placebo-controlled trials were unable to confirm these favorable results, 71,72 and a greater number of side effects were noted in the combination therapy group. 71 Therefore, the use of a combination of a ␤-blocker and ISMN cannot be recommended currently for primary prophylaxis until there is further proof of efficacy.…”
Section: Therapies Not Recommended For Primary Prophylaxismentioning
confidence: 99%
“…69 These results were maintained after 55 months of follow-up, without differences in survival. 70 However, 2 more recent larger doubleblinded, placebo-controlled trials were unable to confirm these favorable results, 71,72 and a greater number of side effects were noted in the combination therapy group. 71 Therefore, the use of a combination of a ␤-blocker and ISMN cannot be recommended currently for primary prophylaxis until there is further proof of efficacy.…”
Section: Therapies Not Recommended For Primary Prophylaxismentioning
confidence: 99%
“…This reduction is smaller than the range of 20 to 26 percent (median, 24 percent) reported in studies of beta-blockers in the primary prophylaxis of variceal hemorrhage [16][17][18][19][20][21][22][23][24] and is probably due to the lower baseline heart rate (median, 73 beats per minute) in our study than in primary-prophylaxis studies of patients with varices (median, 80 beats per minute) 9,17-25 or secondaryprophylaxis studies of patients with varices (median, 84 beats per minute). [26][27][28][29] However, the absolute heart rate achieved is a better indicator of betablockade than the percent reduction in heart rate, 30 and the absolute heart rate in our study during timolol therapy (62 beats per minute) was similar discussion to the median heart rate of 60 beats per minute among patients receiving beta-blockers in previous studies.…”
Section: Hemodynamicsmentioning
confidence: 74%
“…[26][27][28][29] However, the absolute heart rate achieved is a better indicator of betablockade than the percent reduction in heart rate, 30 and the absolute heart rate in our study during timolol therapy (62 beats per minute) was similar discussion to the median heart rate of 60 beats per minute among patients receiving beta-blockers in previous studies. [17][18][19][20][21][22][23][24] The lack of an overall significant change in the HVPG may partly explain our negative results. Although it is possible that positive results could have been obtained if the dose of timolol had been higher, drug intolerance limited our ability to increase the dose further in this group of patients with compensated cirrhosis, most of whom were reluctant to tolerate even minimal side effects.…”
Section: Hemodynamicsmentioning
confidence: 99%
“…In one unblinded study, a significantly lower rate of first hemorrhage was noted in patients receiving combination therapy with nadolol plus ISMN than with nadolol alone [24,73]. However, this finding was not confirmed in larger doubleblinded, placebo-controlled trials that also showed that adverse effects are more common with combination therapy than with b-blockers alone [74,75]. Therefore, it was concluded that a combination of a b-blocker and ISMN could not be recommended for primary prophylaxis.…”
Section: Recommendationsmentioning
confidence: 99%
“…Poor hemodynamic response was found to be the main factor predicting bleeding. HVPG response to drugs is the best predictor of efficacy of prophylaxis of variceal bleeding in patients treated with b-blockers or b-blockers plus nitrates [22,47,51,70,73,74]. The clinical value of HVPG remains unchanged, even when other confounding factors such as the size of varices, presence of red signs, or North Italian Endoscopic Club index were taken into consideration.…”
Section: Recommendationsmentioning
confidence: 99%